Some Equations Concerning the Sum of Divisors Function - Dima, Andreea (The PUMP Journal of Undergraduate Research, 2025)
In this article, I wiil consider four equations involving the sum of divisors function, σ, and I will prove that for the first two there are infinitely many solutions, while for the other two I will provide some particular solutions. I will also study some properties regarding two sequences of numbers.